Pengaruh Model Discovery Learning terhadap Kemampuan Berpikir Kreatif Peserta Didik Pada Pembelajaran Biologi: Tinjauan Literatur - Anugrah, Chici; Heffi Alberida; Fitri Olivia Rahmi (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
Abstract: This study aims to review the literature discussing the impact of the Discovery Learning model on enhancing students' creative thinking skills in Biology education. By reviewing articles published between 2019 and 2024, this research accessed the Google Scholar and ERIC databases using the keywords "Discovery Learning" and "creative thinking skills." The findings of this study indicate that the Discovery Learning model plays a significant role in improving students' creative thinking skills by encouraging active participation in exploration and discovery, which ultimately deepens understanding and enhances problem-solving abilities. Additionally, this model helps students develop analytical skills and their ability to generalize learned concepts. Overall, the Discovery Learning model has proven effective in improving students' creative thinking skills in Biology education. Keywords: Discovery Learning, Creative Thinking, Students, and Biology